Neuroeducation and Cognitive Behavioral Interventions: A Narrative Review - Antonopoulou, Hera (Technium BioChemMed, 2024)
This paper provides a comprehensive narrative review at the intersection of neuroeducation and cognitive behavioral interventions (CBI), exploring how insights from cognitive neuroscience can enhance educational practices. It traces the historical progression of neuroeducation, proposes theoretical frameworks linking reading disabilities with comorbid conditions, and details the methodology underpinning the review. Key themes include the role of neuroplasticity in learning, memory, and cognitive development, and the application of CBIs in managing anxiety and other psychological factors in students. The review emphasizes the need for integrating neuroscientific theories into education, the potential of gamified programs and specialized platforms, and the importance of teachers’ emotional involvement in student learning. Furthermore, it highlights significant gaps in current research and offers practical recommendations for incorporating neuroeducational principles into teacher training and educational policies. The findings underscore the impact of narrative reviews in advancing neuroeducation, pinpoint key interdisciplinary collaborations, and advocate for ongoing research to support innovation and transformation in education.